Photoluminescent Silica Nanostructures and Nanohybrids. Issue 18 (14th July 2022) - Gogoi, Hemen; Banerjee, Subhasree; Datta, Anindya
Abstract: The complicated photophysics of wide variety of defects existing in silica (SiO2 ) layer of nanometer thickness determines widespread photoluminescence bands of Si/SiO2 based system as well as SiO2 nanoparticles (NPs) for their applications in photovoltaic and optoelectronic devices. This review attempts to summarize different photophysical processes in pure SiO2 NPs. Moreover, these NPs also act as scaffolds for various guest molecules to perform their specific functions. Guest fluorophore molecules when trapped inside pores of SiO2 NPs exhibit a different photodynamics than free state, which opens up several important applications of hybrid SiO2 NPs in artificial photosynthesis, sensing, biology and optical fiber. Abstract : All about defective silica : There are two aspects of this minireview: At first, different models describing the photophysics of imperfect SiO2 nanostructures that are believed to be the origin of photoluminescence bands in those nanostructures, are discussed. In the second part, applications of luminescent dye conjugated SiO2 nanostructures in photosynthetic mimic, sensing, biology, therapeutics, and optical fibers, are summarized.